Optimalisasi teknik counter pressure sebagai strategi nonfarmakologis dalam mengatasi nyeri persalinan kala I: Sebuah tinjauan literatur - Ni Luh Putu Mirayanti; Ni Made Dwi Mahayati; Ni Nyoman Suindri (Holistik Jurnal Kesehatan, 2026)
Background: Labor pain is a physiological process experienced by almost all women, especially during the first stage of labor due to uterine contractions and cervical dilation. Pain intensity generally ranges from moderate to severe and can affect the mother's physical and psychological well-being. Inadequate pain management can increase anxiety, prolong labor, and reduce the quality of the birth experience. Therefore, effective and safe non-pharmacological interventions are needed. One method that can be used is the counterpressure technique, which applies pressure to the sacral area to reduce pain perception. Purpose: To analyze the effectiveness of the counterpressure technique in reducing pain intensity during the first stage of labor. Method: This study used a literature review design by examining scientific articles obtained from Google Scholar, PubMed, and ScienceDirect databases. Articles were searched using the keywords "counterpressure," "sacral pressure," and "labor pain." Article selection was based on the PRISMA guidelines, which include identification, screening, due diligence, and inclusion. Inclusion criteria included studies with experimental and quasi-experimental designs published between 2021 and 2026, available in full text, and relevant to the research topic. Results: The counterpressure technique significantly reduced the intensity of first-stage labor pain, with all studies reporting a p-value <0.05. This intervention was effective across a variety of study designs, sample sizes, and pain measurement instruments, such as the Numeric Rating Scale (NRS) and Visual Analogue Scale (VAS). This technique was generally administered during the active phase of labor for 10–30 minutes and showed a reduction in pain intensity from severe to moderate or mild. Conclusion: The counterpressure technique is an effective, safe, and easy-to-implement non-pharmacological intervention for reducing first-stage labor pain. The technique's mechanisms of action include inhibiting pain impulse transmission through gate control theory, increasing endorphin release, and reducing pressure on the sacral region, which also provides a relaxing and comforting effect on the mother. Suggestion: The counterpressure technique is recommended for integration into obstetric care practices, particularly in primary health care facilities. Health workers and midwives are encouraged to receive training in the application of this technique to improve maternal comfort and the quality of the birth experience. Further research is needed to examine the optimal duration and frequency of this intervention to achieve maximum results.   Keywords: Counterpressure; First Stage of Labor; Labor Pain.